Comparative genomics of host adaptive traits in Xanthomonas translucens pv. graminis. (December 2017) - Hersemann, Lena; Wibberg, Daniel; Blom, Jochen; Goesmann, Alexander; Widmer, Franco; Vorhölter, Frank-Jörg; Kölliker, Roland
Abstract Background Xanthomonas translucens pathovars differ in their individual host ranges among Poaceae. As the causal agent of bacterial wilt in Italian ryegrass (Lolium multiflorum Lam.), X. translucens pv.graminis (Xtg ) is one of the most important bacterial pathogens in temperate grassland regions. The genomes of sixXtg strains from Switzerland, Norway, and New Zealand were sequenced in order to gain insight into conserved genomic traits from organisms covering a wide geographical range. Subsequent comparative analysis with previously published genome data of seven non-graminis X. translucens strains including the pathovarsarrhenatheri, poae, phlei, cerealis, undulosa, andtranslucens was conducted to identify candidate genes linked to the host adaptation ofXtg to Italian ryegrass. Results Phylogenetic analysis revealed a tight clustering ofXtg strains, which were found to share a large core genome. Conserved genomic traits included a non-canonical type III secretion system (T3SS) and a type IV pilus (T4P), which both revealed distinct primary structures of the pilins when compared to the non-graminis X. translucens strains.Xtg -specific traits that had no homologues in the otherX. translucens strains were further found to comprise several hypothetical proteins, a TonB-dependent receptor, transporters, and effector proteins as well as toxin-antitoxin systems and DNA methyltransferases. While a nearly complete flagellar gene cluster was identified in one of the sequencedXtg strains, phenotypic analysis pointed to swimming-deficiency as a common trait of the pathovargraminis . Conclusion Our study suggests that host adaptation ofX. translucens pv.graminis may be conferred by a combination of pathovar-specific effector proteins, regulatory mechanisms, and adapted nutrient acquisition. Sequence deviations of pathogen-associated molecular patterns (PAMPs), as observed for the pilins of the T4P and T3SS, are moreover likely to impede perception by the plant defense machinery and thus facilitate successful host colonization of Italian ryegrass.